Understanding Taiwanese Women's Decisional Experiences Regarding Prenatal Screening Procedures And Diagnostics: A Phenomenological Study - Mei-Man Chen; Bi-Hua Cheng (Asian Nursing Research, 2020)
Abstract Purpose: This study sought to understand Taiwanese women’s decisional experiences regarding prenatal screening procedures and diagnostics. Methods: A hermeneutic phenomenological design guided semistructured interviews with 33 women who were 36 weeks pregnant. Data were collected between February and October 2016. Verbatim transcripts were analyzed following hermeneutic circle to cocreate an understanding of Taiwanese women’s decision-making in prenatal screening and diagnostics. Results: Women’s existential experiences were derived from their decision-making process on prenatal screening procedures and diagnostics for chromosomal aneuploidy. These decisional experiences were captured by four theme clusters and eight themes, which were inductively derived from 16 meaning units: (1) accessing health information; (2) considering what was best for my baby; (3) considering family finance; and (4) feeling anxiety posttest. Conclusion: Participants made informed choices on several prenatal screening procedures, ostensibly, based on their personal values and considerations. During the decision-making process, often-cited benefits of genetic screenings were emphasized, but test limitations were often unheeded. A fundamental need for supportive information in decision making was further identified with recommended strategies. Hence, a revision of traditional genetic counseling approaches is recommended. As genomics technologies are increasingly available during antenatal services, women should be sufficiently educated about them to support decision making.